Barriers to Patient-Centered Care and Communication - Amani Ali Alnabi; Qasem Ibrahem Ahmed Almoosa; Abdullatif Khalifa Almubaireek; Abdullah Mohammed Alabdulrahman; Khalifa Yousef Al Atayah; Amanh Habib Al Fayez; Essa Yassen Alsheikh; Ali Hassan Alali; Manal Abdullah Al-Salam; Maryam Abdullah Almusallam; Abdullah Abdulmajeed Mousa Alsuliman; Fatimh Ali Albahrani; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Patient-centered care and effective communication are essential components of quality healthcare delivery. However, several barriers may impede nursery staff from providing optimal patient-centered care and communication with patients and their families. This mini-review examines the barriers faced by nursery staff in delivering patient-centered care and communication and explores evidence-based strategies to address these barriers.